Laboratory Tests and Numerical Simulations of CFRP Strengthened RC Pier Subjected to Barge Impact Load - Sha, Y.; Hao, Hong (World Scientific Publishing Co. Pte. Ltd., 2015)
Bridge piers are designed to withstand not only axial loads of superstructures and passingvehicles but also out-of-plane loads such as earthquake excitations and vessel impact loads.Vessel impact on bridge piers can lead to substantial damages or even collapse of bridgestructures. An increasing number of vessel collision accidents have been reported in the pastdecade. A lot of researches have been conducted for predicting barge impact loads and calculatingstructural responses. However, in practice it is not possible to design bridge structures toresist all levels of barge impact loads. Moreover, with an increasing tra±c volume and vesselpayload in some waterways, the bridge piers designed according to previous speci¯cations mightnot be su±cient to resist the current vessel impact loads. Therefore, strengthening existingbridge piers are sometimes necessary for protecting structures from barge impact. Carbon ¯berreinforced polymer (CFRP) has been widely used in strengthening reinforced concrete structuresunder impulsive loadings. It is an e®ective material which has been proven to be able toincrease the °exural strength of structures. In this study, CFRP composites are used tostrengthen reinforced concrete piers against barge impact loads. Pendulum impact tests areconducted on scaled pier models. Impact force and pier response with and without CFRPstrengthening are compared. The e®ectiveness of using CFRP strengthening the pier model isobserved. In addition, numerical models of the bridge piers are developed and calibrated withexperimental results. Parametric simulations of barge impacting on piers with or without CFRPstrengthening are carried out. The results show that compared with unstrengthened pier, CFRPcomposite strengthened bridge pier has a higher impact resistance capacity and hence enduresless structural damage under the same barge impact load. The e®ectiveness of CFRPstrengthening with di®erent CFRP thickness, CFRP strength and bond strength between thepier and the CFRP composite are also discussed.